Risk-Sharing Networks and Insurance Against Illness. - Weerdt, J; Dercon, S (2006)
Most risk-sharing tests on developing country data are conducted at the level of the village; generally, the full risk-sharing hypothesis is rejected. This paper uses detailed data on all insurance networks within a village in Tanzania; networks are not clustered but largely overlapping. We test whether full risk-sharing occurs within these networks. While village level full-insurance cannot be rejected for food consumption, we find evidence consistent with at least partial insurance of non-food consumption via networks.